Phylogeographic Structure within the Fiddler Crabs Leptuca thayeri and Uca maracoani (Brachyura, Ocypodidae) along the Tropical West Atlantic - Marochi, Murilo Zanetti [UNESP]; Tangerina, Marcelo Marucci Pereira [UNESP]; Rodrigues, Renata de Oliveira [UNESP]; Laurenzano, Claudia; Vilegas, Wagner [UNESP]; Costa, Tânia M. [UNESP]; Schubart, Christoph D. (My University, 2022)
Most fiddler crabs have an extended planktonic larval phase, potentially maintaining gene flow among widely separated populations, in the absence of marine barriers. Such marine barriers could be long coastal stretches without suitable habitat, freshwater plumes caused by large river mouths, or strong currents. Typically, fiddler crabs inhabit mangrove habitats, and as mangroves tend to have a patchy distribution, it is important to gather information on the connectivity between neighboring mangroves and recognize local endemisms. To detect potential genetic differentiation among mangrove-dwelling populations of Leptuca thayeri and Uca maracoani along several thousand kilometers of a tropical coastline, mtDNA sequences of different populations from Brazil and two Caribbean islands were analyzed and compared. As shown in previous studies with fiddler crabs, Brazilian populations are genetically indiscernible, and our data suggest the absence of long-standing gene flow barriers in the two studied species along the Brazilian coast. This includes both sides of the postulated biogeographic barriers corresponding to the split of the Central South Equatorial Current and to the Amazon River freshwater plume. In contrast, conspecific individuals from the Greater Antilles carried different haplotypes, suggesting a biogeographical barrier between Brazil and the Caribbean, apparently having limited gene flow between both regions for extended time periods.
Keywords: Brazil; Caribbean; Cox1 mtDNA; Population genetics; Restricted gene flow